Strategi Pengelolaan Sistem Close Access pada Layanan Perpustakaan - Arlan Arlan (Pusat Publikasi Ilmiah UIN Fatmawati Sukarno Bengkulu, 2017)
In many cases we still can find a close access system in library service in the open access information era. This system is very fragile to meet the library user’s need of information like fast, correctly, and easy to be accessed. How the close access system of library can fulfill the need of library user? By using the methode of literature study, the close access system of library has been analized based of the component of information system which are collections, the arrangement of the collections, information retrieval tools, and library user.